Investigation of mercury concentration and its interaction with zinc and selenium at the muscle and liver tissues of Whitecheek Shark (Carcharhinus dussumieri) from Persian Gulf - A. Tarassoli email ; T. Valinassab; A. Esmaeli Sari (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2013)
Mercury, zinc and selenium concentrations were analyzed in the muscle and liver of 25 Whitecheek Shark (Carcharhinus dussumieri) from the coast of Bandar Abbas. The level of Hg accumulation and its interaction with Zn and Se in Whitecheek Shark were studied. Hg, Zn and Se concentrations were determined by an Advanced Mercury Analyzer (LECO, AMA 254), Atomic Absorption Spectrometer (ASS,PU 9400) and Graphite Furnace Atomic Absorption Spectrophotometry (Perkin Elmer 3030) respectively. The mean (±SD) of Hg, Zn and Se concentrations were 0.05±0.02, 0.92±0.25 and 0.13±0.05μg/g wet wt in the muscle and 1.07±0.86, 1.57±0.43 and 0.46±0.19μg/g wet wt in the liver tissues, respectively. The mean of Hg, Zn and Se in liver tissue was significantly higher than muscle tissue. Also, 64% of liver samples showed levels above the acceptable limit established by WHO and FAO. A positive correlation was found between Hg and Se concentrations in the muscle and liver tissues with weight and length variables were statistically significant. In this study, the accumulation of Se in the muscle and liver of Whitecheek shark showed a positive correlation with Hg concentration. The mean molar ratio of Se to Hg found in the muscle and liver were 6.36±1.77 and 2.74±3.61, respectively. Positive correlations between Hg and Se showed efficient detoxifying mechanism and as a result, the possibility of reduction in